Antibiotic exposure decreases soil arsenic oral bioavailability in mice by disrupting ileal microbiota and metabolic profile. (June 2021) - Li, Meng-Ya; Chen, Xiao-Qiang; Wang, Jue-Yang; Wang, Hong-Tao; Xue, Xi-Mei; Ding, Jing; Juhasz, Albert L.; Zhu, Yong-Guan; Li, Hong-Bo; Ma, Lena Q.
Graphical abstract: Highlights: Soil and antibiotic co-exposure reshaped mouse gut microbiota and metabolic profile. Antibiotic co-exposure decreased As accumulation in mouse kidneys and excretion in urine. Soil bioavailable As pool in the intestinal tract decreased due to reduced amino acids. Transformation from inorganic to organic As was enhanced by the antibiotic perturbed microbiota. Gut microbiota and metabolites played an important role in soil-borne As bioavailability. Abstract: Oral bioavailability of arsenic (As) determines levels of As exposure via ingestion of As-contaminated soil, however, the role of gut microbiota in As bioavailability has not evaluated in vivo although some in vitro studies have investigated this. Here, we made a comparison in As relative bioavailability (RBA) estimates for a contaminated soil (3913 mg As kg −1 ) using a mouse model with and without penicillin perturbing gut microbiota and metabolites. Compared to soil exposure alone (2% w/w soil in diets), addition of penicillin (100 or 1000 mg kg −1 ) reduced probiotic Lactobacillus and sulfate-reducing bacteria Desulfovibrio, enriched penicillin-resistant Enterobacter and Bacteroides, and decreased amino acid concentrations in ileum. With perturbed gut microbiota and metabolic profile, penicillin and soil co-exposed mice accumulated 2.81–3.81-fold less As in kidneys, excreted 1.02–1.35-fold less As in urine, and showed lower As-RBA (25.7–29.0%) compared to mice receiving diets amended with soil alone (56 ± 9.63%). One mechanism accounted for this is the decreased concentrations of amino acids arising from the gut microbiota shift which resulted in elevated iron (Fe) and As co-precipitation, leading to reduced As solubilization in the intestine. Another mechanism was conversion of bioavailable inorganic As to less bioavailable monomethylarsonic acid (MMA V ) and dimethylarsinic acid (DMA V ) by the antibiotic perturbed microflora. Based on in vivo mouse model, we demonstrated the important role of gut microbiota and gut metabolites in participating soil As solubilization and speciation transformation then affecting As oral bioavailability. Results are useful to better understand the role of gut bacteria in affecting As metabolism and the health risks of As-contaminated soils.